PELATIHAN PENGGUNAAN MICROSOFT WORD PADA SISWA SD KELAS VI - Lalu Saparwadi (UNIVERSITAS SERAMBI MEKKAH, 2024)
The development of technology has entered various areas of life, such as economics, health, education, and others. Technology has many benefits, especially in the field of education. Through technology, the sustainability of the learning system will be more effective and efficient. Introducing technology to students is important. One of the basic applications that is very important to introduce to students, especially elementary school students, is Microsoft Word. The purpose of this service is to train elementary school students in using Microsoft Word. This service activity is carried out offline for two meetings. The implementation of this community service activity is carried out through three stages, namely the preparation stage, the implementation stage, and the evaluation stage. The results of this activity can have a positive impact on students. Students can get to know and use Microsoft Word, and can add new knowledge and new skills in using technology.